CLINICAL RESULTS OF THROMBOLYTIC THERAPY WITH ALTEPLASE AND TENECTEPLASE IN PATIENTS WITH MYOCARDIAL INFARCTION - L. A. Bondarenko; L. E. Rudakova; F. K. Rakhmatullov; T. P. Kostrikova; I. I. Kapustina (Столичная издательская компания, 2015)
Aim. To evaluate the clinical results of thrombolytic therapy with thrombolytics (alteplase, tenecteplase) in patients with ST segment elevation myocardial infarction (STEMI). Material and methods. Patients with STEMI (n=181) included in the study were split into two groups depending on the thrombolytic agent: patients treated with alteplase - group 1 (n=78); patients treated with tenecteplase - group 2 (n=52). Patients with STEMI who had no thrombolysis due to late treatment-seeking or the presence of contraindications were included into the group 3 (n=51). Thrombolysis took place both in pre-hospital and in-hospital period. Time before the thrombolysis, STEMI clinical course, mortality , and complications were analyzed. Results. The average time pain-thrombolysis was 2.7±0.22 hours. High efficacy of both thrombolytic drugs was proved in the most of patients. Mortality in patients received thrombolysis was 6.4-7.7%; this in patients without thrombolytic therapy - 24%. Thrombolysis performed in the first 3 hours after STEMI onset reduced mortality to 3.4%. No one intracranial hemorrhage or allergic reaction was registered. Conclusion. Thrombolytic therapy with alteplase and tenecteplase in patients with STEMI in the real clinical practice was high efficient, reduced hospital mortality and induced a few adverse reactions.